Mental health difficulties across childhood and mental health service use: findings from a longitudinal population-based study - Mulraney, Melissa; Hiscock, Harriet; Sciberras, Emma; Coghill, David; Sawyer, Michael (My University, 2020)
Over the past 20 years the prevalence of child and adolescent mental disorders in high-income countries has not changed despite increased investment in mental health services. Insufficient contact with mental health services may be a contributing factor; however, it is not known what proportion of children have sufficient contact with health professionals to allow delivery of treatment meeting minimal clinical practice guidelines, or how long children experience symptoms prior to receiving treatment. To investigate the level of mental healthcare received by Australian children from age 4 years to 14 years. Trajectories of mental health symptoms were mapped using the Strengths and Difficulties Questionnaire. Health professional attendances and psychotropic medications dispensed were identified from linked national Medicare Benefits Schedule (MBS) and Pharmaceutical Benefits Scheme records. Four trajectories of mental health symptoms were identified (low, high-decreasing, moderate-increasing and high-increasing). Most children with mental health symptoms had few MBS mental health attendances, and only a minority received care meeting study criteria for minimally adequate treatment. Children in the high-increasing and moderate-increasing trajectories were more likely to access care, yet there was no evidence of improvement in symptoms. It is important that children and adolescents with mental health problems receive treatment that meets minimal practice guidelines. Further research is needed to identify the quality of care currently provided to children with mental health difficulties and how clinicians can be best funded and supported to provide care meeting minimal practice guidelines. None.
The British Journal of Psychiatry
Keywords: Health and wellbeing